Characterisations of Pre-Descemet’s (Dua’s) layer for its clinical application in keratoplasty - Al-Taan, Saief Laith Muhamed (2018)
There exists a newly discovered, well defined, acellular, strong layer, termed pre-Descemets layer or Dua’s layer (PDL), in the cornea just anterior to the Descemets membrane. This, with the Descemets membrane, separates along the last row of keratocytes in most cases of deep anterior lamellar keratoplasty with the big bubble technique. Recognition of this layer has considerable impact on lamellar corneal surgery, understanding of posterior corneal biomechanics and posterior corneal pathology, such as descemetocele, acute hydrops and pre-Descemets dystrophies.